2016
DOI: 10.1093/brain/aww048
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation modulates synchrony within spatially and spectrally distinct resting state networks in Parkinson’s disease

Abstract: Oswal et al . characterise the effect of deep brain stimulation (DBS) on STN–cortical synchronisation in Parkinson–s disease. They propose that cortical driving of the STN in beta frequencies is subdivided anatomically and spectrally, corresponding to the hyperdirect and indirect pathways. DBS predominantly suppresses the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
258
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(293 citation statements)
references
References 79 publications
26
258
2
Order By: Relevance
“…While β oscillations have dominated the discussion of the pathophysiology of PD, recent studies suggest that the power of these oscillations may not be as important as their coupling with other neural activity both within or across nodes of the motor BGTC circuit, whether in the form of phase amplitude coupling (PAC), coherence, or phase synchronization (de Hemptinne et al, 2013, 2015; Oswal et al, 2016; Ozkurt et al, 2011; Swann et al, 2015; Weiss et al, 2015; van Wijk et al, 2016; Yang et al, 2014). β-broadband γ PAC in the motor cortex (M1) is exaggerated in patients with PD compared to patients with epilepsy or healthy controls and these coupling patterns change with pathological state (de Hemptinne et al, 2013; Swann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While β oscillations have dominated the discussion of the pathophysiology of PD, recent studies suggest that the power of these oscillations may not be as important as their coupling with other neural activity both within or across nodes of the motor BGTC circuit, whether in the form of phase amplitude coupling (PAC), coherence, or phase synchronization (de Hemptinne et al, 2013, 2015; Oswal et al, 2016; Ozkurt et al, 2011; Swann et al, 2015; Weiss et al, 2015; van Wijk et al, 2016; Yang et al, 2014). β-broadband γ PAC in the motor cortex (M1) is exaggerated in patients with PD compared to patients with epilepsy or healthy controls and these coupling patterns change with pathological state (de Hemptinne et al, 2013; Swann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic DBS reduces and nearly eliminates the coupling within M1 motor cortex (de Hemptinne et al, 2015) as does dopaminergic therapy (Swann et al, 2015). Moreover, a recent report shows that STN DBS not only modulates local STN β oscillations, but also suppresses coherence between motor cortices and STN (Oswal et al, 2016). These findings all suggest that pathologic coupling across nodes in the BGTC network may impair normal network function.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical sensorimotor gamma is elevated in PD patients compared to essential tremor and dystonia patients during rest (Crowell et al, 2012;Rowland et al, 2015), hinting at the possibility that the cortical neuronal populations are held at an active state to compensate for the antikinetic beta synchrony in BG (Rowland et al, 2015). In a recent study, it was shown that STN-DBS specifically suppressed the pathological beta synchrony between STN and mesial sensorimotor areas rather than lateral areas (Oswal et al, 2016), and this effect may be driven through the hyperdirect pathway (Gradinaru et al, 2009). We therefore speculate that our observed effect of DBS on low-gamma could be driven via the hyperdirect pathway through the cortico-subcortical functional coupling between the mesial sensorimotor areas and STN.…”
Section: Study III How Do Treatments Modulate Oscillatory Dynamics Inmentioning
confidence: 99%
“…They have showed varied effects of treatments (Abbruzzese and Berardelli, 2003;Conte et al, 2013;Patel et al, 2014), triggering electrophysiological investigations on changes in the cortical and sub-cortical structures during motor tasks (Salenius et al, 2002;Brücke et al, 2008;Hirschmann et al, 2011Hirschmann et al, , 2013 Introduction Introduction suffers from methodological issues (Salenius et al, 2002;Park et al, 2009;Hirschmann et al, 2013;Airaksinen et al, 2015;Cao et al, 2015Cao et al, , 2017Oswal et al, 2016). …”
Section: Chapter -1 Introductionmentioning
confidence: 99%
“…As with all LFP analysis it is difficult to relate these identified changes of the β band to the underlying biology. The current consensus opinion is that the rise in β band activity is related to synchronous oscillatory activity in the cortico-basal ganglia circuits [62].…”
Section: Introductionmentioning
confidence: 99%